PENGARUH PROPORSI DEWAN KOMISARIS WANITA, PROPORSI DEWAN KOMISARIS INDEPENDEN, DAN STRUKTUR KEPEMILIKAN ASING TERHADAP KINERJA PERUSAHAAN PADA SEKTOR TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020 - Kusuma, Regina Deandra (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
This study aims to examine the effects of the variables of the proportion of female board of commissioners, the proportion of independent board of commissioners, and foreign ownership structure on the company performance, proxied by return on assets (ROA), of transportation and logistics companies listed on the Indonesia Stock Exchange in 2020. The research adopts a quantitative approach and utilizes annual financial data obtained from the official websites of the companies and IDX. Data collection is conducted through documentation study and literature review. All collected data are processed using SPSS 26. The results of this study demonstrate that the variables of the proportion of female board of commissioners, the proportion of independent board of commissioners, and foreign ownership structure collectively have a significant impact on the financial performance of the companies, proxied by return on assets (ROA). Specifically, the variable of the proportion of independent board of commissioners has a positive and significant influence on the financial performance of the companies. However, the variables of the proportion of female board of commissioners and foreign ownership structure do not show evidence of their impact on the company's performance.